Euonymus semenovii Regel & Herder as an Important Element of Relict Forests: A Summary of Research Experience. - Kirillov, V.Yu.; Stikhareva, T.N.; Ivashchenko, A.A.; Daulenova, M.Zh.; Dukenov, Zh.S. (Karagandy University of the name of acad. E.A. Buketov, 2025)
The article examines the scientific information available on Euonymus semenovii Regel & Herder, a relict species of flora found in Central Asia and China. The article explores several aspects, including distribution, morphological and ecological characteristics, phytocenotic features, introduction experiences, and conservation issues. Euonymus semenovii demonstrates wide plasticity and can thrive in moist habitats, withstand some drought, and grow at various altitudes (1100-3200 m above sea level). These characteristics are reflected in the morphological features and coloration of its individual organs. The species is typically found in small abundance in the understory of various types of mountain forests. The composition of plant communities involving E. semenovii varies across its range, ranging from apple forests (Malus sieversii M. Roem) to spruce forests (Picea schrenkiana Fisch & C.A. Mey). Euonymus semenovii is considered a relict species in relict plant communities, such as those with Celtis caucasica Willd and Atraphaxis muschketowii Krasn in Kazakhstan. Euonymus semenovii also plays a significant role in landslide succession processes in the mountain forests of the Northern Tien Shan, highlighting its environmental and anti-erosion importance for maintaining the stability of mountain ecosystems. The article suggests practical uses and conservation strategies for E. semenovii. It emphasizes the need for further in-depth research on the species to fully understand its potential and the importance of systematic monitoring observations and the development of accelerated propagation methods.
Keywords: Celastraceae; Euonymus semenovii Regel & Herder; distribution; morphology; phytocoenology; economic importance; introduction; conservation